The Effect of Red Rosella Tea on Blood Glucose Individuals with Diabetes Mellitus Type II - Erni Tri Indarti (Jurnal Ilmiah Kesehatan, 2022)
Red rosella petals had potential as diabetes therapy. Red rosella petals contain citric acid, malic acid, Vitamin C, anthosinins, proteins and flavonoids that act as antioxidants that help lower pancreatic beta-cell damage and improve insulin work. Red rosella petals can be dried without reducing the content in it. Practically, it is used as a beverage ingredient, namely tea. This research aimed to analyze red rosella tea's effect on blood glucose in individuals with diabetes mellitus type II. This research was pre-experimental research with one-group pre-post-test design approach. The population was 17 individuals in Ketawang Village, Gondang District. The sample was 14 respondents with a proportional stratified random sampling technique. The independent variable was rosella tea, and the dependent variable was blood glucose. The instruments were red rosella tea with Standard operating procedures. The data was analyzed SPSS 21 paired t-test with a significance level of 0.05. The results showed that 14 respondents had an average blood glucose level of 317,64 mg/dl before the intervention, while after giving red rosella tea for 7 days had an average of 222 mg/dl. In addition, the results of the paired t-test, p-value = 0.00 ≤ α (0.05). Thus, there was an Effect of Red Rosella Tea on Blood Glucose in individuals with Diabetes Mellitus Type II. Red Rosella Tea can decrease Blood Glucose. Individuals with diabetes mellitus type II should consume red rosella tea routinely to avoid the complications of diabetes mellitus.